2011
DOI: 10.1097/jom.0b013e31822e0940
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Mortality Among Aircraft Manufacturing Workers

Abstract: This large, long-term cohort study with comprehensive exposure assessment found no consistent evidence of increased cancer risk overall or by site among aircraft workers, including those with long-term exposure to TCE, PCE, and mixed solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
(43 reference statements)
2
37
0
Order By: Relevance
“…All cohort16 22 24 26 27 31–40 and case–control11 17 18 41–50 studies included in this analysis are summarised in supplementary table S1. For each study, data regarding study size, location, exposure assessment methods, risk estimates, and person-years and length of follow-up (for cohort studies) are provided.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All cohort16 22 24 26 27 31–40 and case–control11 17 18 41–50 studies included in this analysis are summarised in supplementary table S1. For each study, data regarding study size, location, exposure assessment methods, risk estimates, and person-years and length of follow-up (for cohort studies) are provided.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, three US studies utilising the same cohort in Utah have been published,20–22 but only the most recent cohort follow-up study was selected 22. Likewise, two US studies conducted on one Californian cohort study have been published,23 24 but only results from the extended follow-up study were utilised for this analysis 24. Also identified were two studies utilising the same cohort with different inclusion criteria 25 26.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anttila et al ,17 in a cohort study of 849 Finnish workers biologically monitored for perchloroethylene exposure between 1974 and 1983, observed a non-significant excess of kidney cancer among workers relative to the number expected from population rates (SIR 1.8, 95% CI 0.2 to 6.5), based on two observed cases of kidney cancer. Lipworth et al 18 updated follow-up of a cohort of aircraft manufacturing workers exposed to different solvents who were assessed for perchloroethylene exposure using a JEM based on job descriptions and historical chemical usage patterns; for 5830 workers assessed as having intermittent or routine perchloroethylene exposure, the SMR for kidney cancer was 0.8 (0.4 to 1.4; 13 deaths). In the most recent follow-up of a cohort of 1704 workers in dry cleaning facilities with documented records of perchloroethylene use, Calvert et al 19 reported an SMR of 1.14 (0.37 to 2.67); in an analysis restricted to participants exposed only to perchloroethylene, a SMR of 1.35 (0.16 to 4.89) was observed.…”
Section: Discussionmentioning
confidence: 99%
“…a Tissues shown represent those for which limited or sufficient evidence of human cancer hazard effects associated with TCE or PCE were available, as determined by IARC (IARC, 2014) b Section 6.3 "Overall characterization of TCE Hazard and Dose Response" (US EPA, 2011b) c Renal cell adenoma/carcinoma observed in rats exposed to PCE for two years, however this was only statistically significant when compared with historical controls (NTP, 1986 relative risks above one (Raaschou-Morgan et al, 1998;Persson and Fredrikson, 1999;Raaschou-Nielsen et al, 2003;Radican et al, 2008;Wang et al, 2009;Lipworth et al, 2011;Christensen et al, 2013;Cocco et al, 2013;Hansen et al, 2013). However, no association was found in some studies, which could be attributed to methodological limitations in the design or analysis or low prevalence of TCE exposure [Boice et al, 2006 (based on 1 case); Bahr et al, 2011;Vlaanderen et al, 2013;Bove et al, 2014;Silver et al, 2014].…”
Section: Cancermentioning
confidence: 99%